Numerical prediction of fatigue threshold of metallic materials in vacuum. (July 2019) - Antunes, F.V.; Prates, P.A.; Camas, D.; Sarrazin-Baudoux, C.; Gardin, C.
Highlights: A numerical procedure was developed to predict effective fatigue threshold. The numerical predictions are double of the experimental values. The difference was attributed to environmental effects. The numerical predictions seem to be valid for vacuum conditions. Abstract: The fatigue threshold is determined experimentally following international standards, but its measurement is laborious and time consuming. This paper proposes a numerical approach to determine the fatigue threshold based on the analysis of the crack tip opening displacement, CTOD, evaluated using the finite element method. It assumes that fatigue crack propagation only occurs with plastic deformation at the crack tip. However, a factor of about two was found between the numerical predictions and experimental results of effective fatigue threshold from literature. This difference was attributed to a different mechanism of fatigue crack growth at relatively low load ranges, resulting from environmental effects at the crack tip. Therefore, the approach proposed is adequate to predict the fatigue threshold in vacuum, which is supposed to be controlled by crack tip plastic deformation.